Symptomatic isolated metastasis from an asymptomatic primary tumor - Sukhdev Pandey; Amit Tuli; Kim Jacob Mammen (Wolters Kluwer Medknow Publications, 2018)
Renal cell carcinoma (RCC) is the second most common among all genitourinary malignancies. With the advent of radiological imaging, the presenting triad of fever, hematuria, and abdominal mass is rarely seen. Osseous metastasis of RCC is the second most frequent location after lung metastases. They rarely present as a symptomatic-isolated lesion with an asymptomatic primary tumor. We have identified an unusual facet of the metastatic pattern of this tumor in its unusual propensity to metastasize to the scapula. Scapular metastasis when present, is frequently large, and is generally not part of a picture of disseminated disease. We present a case of symptomatic metastasis with asymptomatic primary (RCC).